2014
DOI: 10.1093/mnras/stu2136
|View full text |Cite
|
Sign up to set email alerts
|

Iron K and Compton hump reverberation in SWIFT J2127.4+5654 and NGC 1365 revealed by NuSTAR and XMM–Newton

Abstract: In the past five years, a flurry of X-ray reverberation lag measurements of accreting supermassive black holes have been made using the XMM-Newton telescope in the 0.3-10 keV energy range. In this work, we use the NuSTAR telescope to extend the lag analysis up to higher energies for two Seyfert galaxies, SWIFT J2127.4+5654 and NGC 1365. X-ray reverberation lags are due to the light travel time delays between the direct continuum emission and the reprocessed emission from the inner radii of an ionised accretion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 65 publications
6
73
1
Order By: Relevance
“…Soft-band X-ray reverberation lags were indeed discovered with XMM-Newton in the narrow line seyfert 1 (NLS1) galaxy 1H0707-495 (Fabian et al 2009), and in other bright Seyferts (Emmanoulopoulos et al 2011;De Marco et al 2013). High-frequency iron Kα reverberation lags have also been detected in a small number of Seyfert galaxies (Zoghbi et al 2012(Zoghbi et al , 2013Kara et al 2013a,b), while similar lags have been reported for the Compton hump in a few sources as well Kara et al 2015).…”
Section: Introductionsupporting
confidence: 53%
“…Soft-band X-ray reverberation lags were indeed discovered with XMM-Newton in the narrow line seyfert 1 (NLS1) galaxy 1H0707-495 (Fabian et al 2009), and in other bright Seyferts (Emmanoulopoulos et al 2011;De Marco et al 2013). High-frequency iron Kα reverberation lags have also been detected in a small number of Seyfert galaxies (Zoghbi et al 2012(Zoghbi et al , 2013Kara et al 2013a,b), while similar lags have been reported for the Compton hump in a few sources as well Kara et al 2015).…”
Section: Introductionsupporting
confidence: 53%
“…Given that the corona emission is inhomogeneous and the scale height varies with distance in our model, the X-ray reflection emissivity is expected to differ from these simplified models. Kara et al (2015Kara et al ( , 2016 point out that the true light-travel time between the corona and the disk is longer than the observed lag measured by X-ray reverberation due to dilution effects. The direct emission from the corona, as our model reveals, unavoidably contributes a fraction to the reflection band.…”
Section: Radiation Compactness Of the Coronamentioning
confidence: 93%
“…Along this line of investigation, significant efforts have been directed toward observationally constraining the corona geometry. It is found that the coronal illumination may originate from a height less than 10R g (Detailed data analyses on the reverberation lag and deduced height of the corona can be found in Fabian et al 2009Fabian et al , 2015De Marco et al 2013;Kara et al 2013Kara et al , 2015Kara et al , 2016Reis & Miller 2013).…”
Section: Radiation Compactness Of the Coronamentioning
confidence: 99%
“…To the contrary, Miller et al (2010) proposed that the soft X-ray lags of 1H 0707−495 can be accounted for by reverberation due to much more distant matter. Up to now, similar soft lags are detected in a number of NLS1s (e.g., Kara et al 2015), but their origins are not fully understood. Meanwhile, Mizumoto, Ebisawa, & Sameshima (2014) (hereafter, Paper I) successfully explained the rapid variation of 1H 0707−495 by the "variable double partial covering" (VDPC) model in the 0.5-10 keV.…”
Section: Introductionmentioning
confidence: 91%